Relieving Accommodative Spasm: Two Case Reports. - Satgunam, Prem Nandhini (Optometry & Visual Performance, 2018)
Background: Relief from accommodative spasm involves a long course of pharmacological treatment and/or vision therapy. Complete resolution is challenging, especially within a short time frame. This case report demonstrates a clinical management technique that instantaneously provided relief from accommodative spasm. A fogging technique modified from Borish's delayed subjective test was used to stabilize accommodation in two patients. Case Report 1: A 14-year-old male child presented with 20/200 visual acuity and variable high myopic refractive error. Cycloplegic refraction showed low hyperopia. Atropine was used for 1.5 months. Upon discontinuation of the atropine, the child again developed accommodative spasm and was referred to our vision therapy clinic. Case Report 2: A 10-year-old male child presented with 20/500 visual acuity and high myopia but showed low hyperopia upon cycloplegic refraction. At the post-cycloplegic visit, the child again exhibited accommodative spasm and was referred to our vision therapy clinic. Conclusion: A modified fogging technique can be applied to relieve accommodative spasm for patients through optical means. A cycloplegic refraction is essential to determine the refractive error initially. The modified fogging technique can be applied during the post cycloplegic visit if the spasm recurs. Stability of accommodation and improvement in visual acuity is obtained with this technique.